Effects Of Film Thickness On The Sensitivity Of Tin (IV) Oxide Gas Sensor In Detecting Various Concentrations Of Benzene And Toluene Gases - Teoh, Xuan Chee (Universiti Sains Malaysia, 2021)
Tin (IV) oxide (SnO2) gas sensor is the most commonly used metal oxide semiconductor gas sensor in various industries due to its high stability and reliability. In addition to the experimental works, mathematical models are also important in studying the responses os the SnO2 gas sensor when it is exposed to a variety of operating conditions and targeted gases. In the present study, a mathematical model is developed based on Knudsen diffusion model which is commonly used to describe tha gas diffusion mechanism. Previous researches had shown that the sensing performance of SnO2 gas sensor is influenced by some factors, such as operating temperature, targeted gas concentration, film thickness and pore radius of the sensing film. On top of this, in order to determine the reliability and feasibility of the develop mathematical model, MATLAB simulation is used to study the effects of targeted gas (benzene and toluene) concentration (